3D in silico study of magnetic fluid hyperthermia of breast tumor using Fe3O4 magnetic nanoparticles. (July 2020) - Suleman, Muhammad; Riaz, Samia
Abstract: Modeling and simulation of the temperature distribution, the mass concentration, and the heat transfer in the breast tissue are hot issues in magnetic fluid hyperthermia treatment of cancer. The breast tissue can be visualized as a porous matrix with saturated blood. In this paper, 3D in silico study of breast cancer hyperthermia using magnetic nanoparticles (MNPs) is conducted. The 3D FEM models are incorporated to investigate the infusion and backflow of nanofluid in the breast tumor, the diffusion of nanofluid, temperature distribution during the treatment, and prediction of the fraction of tumor necrosis while dealing with the thermal therapy. All the hyperthermia procedures are simulated and analyzed on COMSOL Multiphysics. The sensitivity of frequency and amplitude of the applied magnetic field (AMF) is investigated on the heating effect of the tumor. The mesh dependent solution of Penne's bioheat model is also analyzed. The simulated results demonstrate successful breast cancer treatment using MNPs with minimum side effects. Validation of current simulations results with experimental studies existing in literature advocates the success of our therapy. The increase in the amplitude and frequency of the AMF increases of the temperature in the tumor. The variation of mesh from coarser to finer increased the temperature through small fractions. We have also simulated the magnetic induction problem where the magnetic field is generated by current-carrying coil conductors induce heat in nearby breast tumors due to excitation of MNPs by magnetic flux. This research will aid treatment protocols and real-time clinical breast cancer treatments. Graphical abstract: Image 1 Highlights: 3D in silico study of magnetic fluid hyperthermia of breast tumor is conducted. Infusion, diffusion, and heat transfer in breast cup are simulated on COMSOL Multiphysics. The backflow of nanofluid and fraction of tumor necrosis in breast cup is predicted quantitatively. The sensitivity of heating parameters and magnetic field arises due to current carrying coil to heat tumor is investigated. Mesh dependent solution of the bioheat transfer model in breast cup is analyzed.